Profile of use of off-label and non-licensed drugs in a neonatal Intensive Care Unit (Research, Society and Development, 2024)
Objective: The off-label drug prescription is unavoidable in neonatal and pediatric clinical practice and its use may result risks. This study was conducted to characterize the epidemiological profile of off-label and/or unlicensed drugs prescribed to patients in a neonatal intensive care unit of a high-complexity exclusively pediatric hospital in Brazil. Methods: descriptive and cross-sectional study, including all medical prescriptions for the year 2019. Data were expressed as mean and median, or absolute and relative frequency. Results: 24,787 prescription items were recorded for 102 medications. Of these, 58% were off-label and 25% unlicensed. The most prescribed drug classes were anti-infective and central nervous system drugs. Moreover, 12% were classified as high-surveillance drugs, principally fentanyl (51.0%) as the main drug. Conclusion: this study reinforces the importance of the pharmacist as a fundamental strategy in understanding the epidemiological profile of drugs used in neonatology and the potential adverse reactions that these drugs can cause.